2020
DOI: 10.3168/jds.2019-17415
|View full text |Cite
|
Sign up to set email alerts
|

New function of the CD44 gene: Lipid metabolism regulation in bovine mammary epithelial cells

Abstract: The CD44 gene encodes a cell-surface glycoprotein that participates in a variety of biological processes such as cell interactions, adhesion, hematopoiesis, and tumor metastasis. We compared the transcriptome in bovine mammary epithelial cells (bMEC) of Chinese Holstein dairy cows producing milk of high and low fat contents. Our results suggest that CD44 might be a candidate gene affecting milk fat synthesis. In the present study, the overexpression of the CD44 gene increased the contents of intracellular trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In addition to participating in immune and inflammation-related regulation, CD44 antigen plays a key regulatory role in the lipid metabolism of bovine mammary epithelial cells. Both triglyceride and cholesterol contents are augmented in cells with overexpression and conversely reduced in cells with knockdown of CD44 ( Jiang et al, 2020 ), thus suggesting its critical role in regulating lipid components of bovine milk. The hyaluronic acid-binding domain of CD44 antigen is N-glycosylated and the N-glycans of this domain could weaken hyaluronic acid binding upon capping the terminal with sialic acid residues ( Guvench, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to participating in immune and inflammation-related regulation, CD44 antigen plays a key regulatory role in the lipid metabolism of bovine mammary epithelial cells. Both triglyceride and cholesterol contents are augmented in cells with overexpression and conversely reduced in cells with knockdown of CD44 ( Jiang et al, 2020 ), thus suggesting its critical role in regulating lipid components of bovine milk. The hyaluronic acid-binding domain of CD44 antigen is N-glycosylated and the N-glycans of this domain could weaken hyaluronic acid binding upon capping the terminal with sialic acid residues ( Guvench, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both PRMT1 and CHTOP were significantly reduced ( p < 0.001) suggestive of impaired glucose metabolism already at P0. Conversely, genes involved in lipid metabolism and production of triglycerides and cholesterol (CD44 ( Jiang et al, 2020 ), Lipase E (LIPE) ( Gu et al, 2019 ), mitochondrial Glycerol 3 Phosphate Dehydrogenase (GPD2) ( Mráček et al, 2013 ) were also altered. While CD44 was significantly increased ( p < 0.001), LIPE and GPD2 were significantly reduced ( p < 0.01) in the mutant septa ( Figure 7C ).…”
Section: Resultsmentioning
confidence: 99%
“…To verify the role of the GPAM gene in triglyceride synthesis, experiments have been carried out on mice; this research suggested that the GPAM gene has various effects after knockout, including lighter gonadal fat pads, reduced weight, reduced plasma triglyceride levels and decreased liver triglyceride content. Thus, these results strongly suggest that the GPAM gene has a vital role in the synthesis of triglycerides in liver and plays a considerable role in the regulation of the fatty acid components of glycerophosphatides (Dawson et al, 2006;Jung et al, 2013). This result is consistent with our previous work (Yu et al, 2017), which found that the GPAM gene influences the TG content in bovine fetal fibroblasts (BFFs), the knockdown of the GPAM gene could cause the triglyceride in BFFs to significantly decrease and the overexpression of GPAM gene significantly increased the TG level compared with the BFF control group.…”
Section: Discussionmentioning
confidence: 80%